Soup : superb ways with a classic dish - Mayhew, Debra (New York, NY : Hermes House, 1999)
This book includes more than 200 delectable, world-wide selection of enticing soups of all styles, including chilled, creamy, rich, exotic, spicy, fruity, hearty and lavish.
Includes index.
107026
Keywords: Soups; Cooking